KEBERLANJUTAN PENGELOLAAN KAWASAN KONSERVASI PENYU DI PANTAI PANGUMBAHAN, SUKABUMI, JAWA BARAT - M. Apuk Ismane; Cecep Kusmana; Andi Gunawan; Ridwan Affandi; Surachman Suwardi (Graduate School Bogor Agricultural University (SPs IPB), 2018)
accordance with high exploitation of turtle in several sectors and will threatened the turtle sustainability in the future. The aim of this study is to analyze the situational condition of environmental biophysics, socio-economic of the population, and the potential of tourism object in Pangumbahan Beach turtle conservation area and to determine the sustainability status of conservation area management for ecotourism development. Descriptive, vegetation, situational, tourist attraction, and sustainability status analysis are used for this research. Result of Situational analysis shows community attitudes toward turtle conservation management mostly uncertain (44%) about the turtle conservation. Generally the condition of the green turtle nesting habitat at Pangumbahan Beach were categorized as appropriate to very appropriate based on habitat sustainability matrix of green turtle nesting. Turtle conservation sustainability index in Pangumbahan Beach of all dimensions are sustainable.